Doing the Lord’s Work: Deconstructing Fundamentalist Christianity Through Cathartic Anti-Fandom on Reddit - Caitlin E. Lawson; Cecilia R. Hafferty (Social Media + Society)
r/fundiesnarkuncensored is a Reddit community that monitors and critiques fundamentalist Christian, namely evangelical, content creators. Many members of the community were formerly conservative Christians who have since deconstructed some or all of their beliefs. This study approaches “fundie snarkers,” particularly those who have deconstructed, through the lenses of anti-fandom and affect theory, to deepen our understanding of anti-fandom as a simultaneously ideological and affective phenomenon. Through individual, semi-structured interviews with 20 members of r/fundiesnarkuncensored, we explore the role that “fundie snarking” plays in members’ deconstruction journeys and vice versa. Participants organized content on the subreddit into three categories based on their affective and intellectual responses to that content: petty snark, or superficial critiques that participants find both guiltily pleasurable and frustratingly rude; structural snark, or systemic critiques of fundamentalism that participants universally esteem; and dark snark, or content that participants find too distressing to engage. Taken together, this “structure of snark” reveals the ambiguity of their anti-fandom by emphasizing that participants have empathy for the fundies they criticize and see the subreddit’s ideal purpose as a tool for deconstruction. Ultimately, through our discussion of the gratifications participants obtain through their engagement with the subreddit, we propose an additional form of anti-fandom: cathartic anti-fandom. Cathartic anti-fandom involves the dislike and critique of ideologies, practices, and communities in which the anti-fan formerly participated and/or by which they were harmed. By filtering fundamentalist Christian teaching through critical commentary and making these ideologies laughable, r/fundiesnarkuncensored provides an accessible and enjoyable space for members to unlearn harmful ideologies.